Cognitive Behavioral Therapy Reduces Benzodiazepine Anxiolytics Use in Japanese Patients with Mood and Anxiety Disorders: A Retrospective Observational Study - Nakajima A (Dove Medical Press, 2020)
Aiichiro Nakajima,1 Ayako Kanie,1 Masaya Ito,1 Naotsugu Hirabayashi,2 Fumi Imamura,3 Yoshitake Takebayashi,1,4 Masaru Horikoshi1 1National Center for Cognitive Behavior Therapy and Research, National Center of Neurology and Psychiatry, Tokyo, Japan; 2Department of Psychiatry, National Center of Neurology and Psychiatry, Tokyo, Japan; 3Department of Clinical Psychology, National Center of Neurology and Psychiatry, Tokyo, Japan; 4Department of Health Risk Communication, School of Medicine, Fukushima Medical University, Fukushima, JapanCorrespondence: Aiichiro NakajimaNational Center for Cognitive Behavior Therapy and Research, National Center of Neurology and Psychiatry, 4-1-1, Ogawahigashi, Kodaira, Tokyo 187-8551, JapanTel +81-42-341-2711Fax +81-42-346-1944Email aiichiro.nakajima@ncnp.go.jpPurpose: Benzodiazepines (BZDs) are prescribed to treat psychiatric diseases. However, many guidelines recommend limiting the use of BZDs because of side effects and lack of evidence regarding long-term efficacy. Moreover, reducing BZDs’ use is difficult because of dependency and the severity of withdrawal symptoms. The efficacy of cognitive behavioral therapy (CBT) for mood and anxiety disorders has been demonstrated. However, there is scant evidence that CBT has effectively reduced BZDs use, especially in Japan, where the BZDs prescription rate is high. Therefore, we sought to examine the impact of CBT on reducing BZDs use in a Japanese psychiatric setting.Patients and Methods: Participants were outpatients with mood and anxiety disorders who were prescribed BZD anxiolytics. We retrospectively reviewed changes in BZD anxiolytics prescription dosages during CBT (66 patients; mean number of CBT sessions, 14.6) from our hospital record between April 2015 and September 2017. We checked prescriptions at four time points: at first interview for judging adaptation of CBT (baseline), at the first CBT session, at the last CBT session, and 3 months after the last CBT session.Results: A total of 13 of 66 patients discontinued BZD anxiolytics during CBT, and 21 of 66 reduced their prescribed dosage by 50%. The association between discontinuation and dose-reduction and assessment period was modeled simultaneously using Bayesian hierarchical hurdle model. Results from the modeling showed a significant discontinuation at post-CBT and at 3 months post-CBT session compared to baseline (estimated median odds ratio [OR] post-CBT = 9.79 [95% CI: 4.65– 20.45]; OR at 3 months post-CBT = 11.53 [95% CI: 6.06– 22.33]). Moreover, a significant dose reduction was observed post-intervention (estimated median relative risk = 0.845 [95% CI: 0.729– 0.982]), with a median reduction of 1.7 mg (diazepam conversion) in BZD use.Conclusion: Our results suggest that CBT possibly aids in reducing and discontinuing BZD anxiolytics use for Japanese patients.Keywords: psychiatric diseases, depression, acquired dependency, discontinuation